Assessment of the Inhibitory Effect of Rifampicin on Amyloid Formation of Hen Egg White Lysozyme: Thioflavin T Fluorescence Assay versus FTIR Difference Spectroscopy - Gang Ma; Hong Zhang; Jianhua Guo; Xiaodan Zeng; Xiaoqian Hu; Wenying Hao (Journal of Spectroscopy)
The inhibitory effect of rifampicin on the amyloid formation of hen egg white lysozyme was assessed with both Thioflavin T (ThT) fluorescence assay and Fourier transform infrared (FTIR) difference spectroscopy. We reveal that ThT fluorescence assay gives a false positive result due to rifampicin interference, while FTIR difference spectroscopy provides a reliable assessment. With FTIR, we show that rifampicin only has marginally inhibitory effect. We then propose that FTIR difference spectroscopy can potentially be a convenient method for inhibitor screening in amyloid study.